The Last Sin Eater - Rivers, Francine 1947- (Carol Stream, Ill. Tyndale House Publishers, 2013)
Cadi Forbes, having seen the sin eater the night her Granny was buried, embarks on a forbidden quest to find the man who can free her and her mother from the sin that plagues their lives.
Keywords: Mountain life -- Fiction; Young women -- Fiction; Atonement -- Fiction; Great Smoky Mountains (N.C. and Tenn.) -- Fiction; Historical fiction; Christian fiction; Bildungsromans